Strategies for Shaping Students’ Religious Character Through Islamic Education at Madrasah Tsanawiyah - Mawardi Pewangi; Ferdinan Ferdinan (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the implementation of Islamic Religious Education (IRE) as a strategic instrument in shaping students’ religious character at Madrasah Tsanawiyah Datarang. The research employs a descriptive qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and documentation of religious activities in the school environment. The findings reveal that the implementation of IRE is carried out through two main strategies: value-based formal learning using interactive lectures, thematic discussions, and religious case studies; and the habituation of Islamic values through routine programs such as morning Qur’anic recitation (tadarus), congregational dhuha prayers, and the school culture of greetings, smiles, and polite interaction (3S). The exemplary role of teachers and the synergy between school and family are key factors in the internalization of religious values. However, challenges such as inconsistency in teachers’ behavior and external environmental influences still need to be addressed collaboratively. This study concludes that reflective and contextual implementation of IRE has proven effective in sustainably developing students' religious character.